2019
DOI: 10.1002/slct.201803716
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Doped Carbon Quantum Dots as a “Turn‐Off” Fluorescent Probes for Highly Selective and Sensitive Detection of Mercury(II) Ions

Abstract: A facile, economical and straightforward hydrothermal strategy was used to prepare highly luminescent nitrogen‐doped carbon quantum dots (N‐CQDs) by using citric acid and urea as the precursors. The as‐prepared N‐CQDs exhibited excellent excitation‐wavelength‐dependent photoluminescence property, high relative fluorescence quantum yield of up to 82.4%, and high selective response to Hg2+ over other examined metal ions in water samples. Under the optimal conditions, the response was linearly proportional to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Here the quenching mechanism between CQDs and trifluralin was investigated by the Stern‐Volmer equation. According to the results of Stern‐Volmer plot shown in Figure S1, the Stern‐Volmer constant (Ksv) was 0.00389, 0.00339 and 0.00300 at 277 K, 298 K, and 308 K, respectively, demonstrating the Ksv values were decreased with increase of temperature from 277 to 308 K. The above results indicated that the quenching mechanism was a static quenching process …”
Section: Resultsmentioning
confidence: 73%
“…Here the quenching mechanism between CQDs and trifluralin was investigated by the Stern‐Volmer equation. According to the results of Stern‐Volmer plot shown in Figure S1, the Stern‐Volmer constant (Ksv) was 0.00389, 0.00339 and 0.00300 at 277 K, 298 K, and 308 K, respectively, demonstrating the Ksv values were decreased with increase of temperature from 277 to 308 K. The above results indicated that the quenching mechanism was a static quenching process …”
Section: Resultsmentioning
confidence: 73%
“…44 The absorption peak at 1589 cm −1 results from the asymmetry CO stretching vibrations, and the peaks at 1396 cm −1 and 1211 cm −1 are caused by the C–N and C–O stretching vibrations, respectively. 45–47 The above FT-IR spectroscopic results clearly indicate that N has been successfully doped into the NCDs. Furthermore, the NCDs are rich in hydrophilic surface functional groups like hydroxyl, amino, and carboxyl groups, which contribute to their good water solubility and may be attributed to the low carbonization temperature.…”
Section: Resultsmentioning
confidence: 70%
“…Clearly, K SV decreases with increasing reaction temperature, that is, as the temperature rises, the fluorescence quenching effect diminishes, confirming the assumption that the quenching principle is primarily static quenching. 47,59,60 It is speculated that this may be due to the strong affinity of Hg 2+ for the surface functional groups (such as carboxyl groups) on the NCDs, which can chelate with them to form non-fluorescent complexes, resulting in a decrease in fluorescence intensity. Therefore, we conclude that the quenching mechanism of NCDs by Hg 2+ is mainly through static quenching, possibly due to the formation of non-fluorescent complexes between Hg 2+ and the surface functional groups on NCDs.…”
Section: àmentioning
confidence: 99%
“…21 According to some researches, these uorescence sensors are characterized by their sensitivity and selectivity largely due to the affinity of active groups (such as amino and sulydryl) on the CQDs surface for the ions they detect. [22][23][24] Hence, because meso-2,3-dimercaptosuccinic acid is rich in sulydryl groups and able to do react with citric acid at high temperature and pressure, the meso-2,3-dimercaptosuccinic acid was used as the sulfur source to synthesize successfully the sulydryl functionalized carbon quantum dots (HS-CQDs). This one-pot preparation route is very easy, green and ecofriendly and was successful at introducing sulydryl functional groups.…”
Section: Introductionmentioning
confidence: 99%
“… 21 According to some researches, these fluorescence sensors are characterized by their sensitivity and selectivity largely due to the affinity of active groups (such as amino and sulfhydryl) on the CQDs surface for the ions they detect. 22–24 …”
Section: Introductionmentioning
confidence: 99%